Response‐based modification of CHOP chemotherapy for canine B‐cell lymphoma. (26th March 2021) - Benjamin, Sarah E.; Sorenmo, Karin U.; Krick, Erika L.; Salah, Pascale; Walsh, Koranda A.; Weinstein, Nicole M.; Keuler, Nicholas S.; Avery, Anne C.; Atherton, Matthew J.; Lenz, Jennifer A.
Abstract: Despite high initial response rates, a subset of dogs with B‐cell lymphoma responds less robustly to CHOP‐based chemotherapy and experiences shorter survival. One hundred and four dogs with nodal B‐cell lymphoma were treated with a response‐based CHOP (RBCHOP) protocol modified based on response to individual drugs during the first chemotherapy cycle. Dogs achieving complete (CR) or partial response (PR) at week 3, following treatment with vincristine and cyclophosphamide, received RBCHOP 1 (n = 72), a protocol sequentially rotating vincristine, cyclophosphamide, and doxorubicin. Dogs without a detectable response at week 3 that subsequently achieved CR or PR following treatment with doxorubicin received RBCHOP 2 (n = 14), in which four doses of doxorubicin were given consecutively followed by vincristine and cyclophosphamide. Dogs that failed to respond at week 3 and then to doxorubicin at week 5 assessment were offered rescue chemotherapy (RBCHOP 3, n = 18). Median progression free survival (PFS) and overall survival time (OST) were similar between RBCHOP 1 (PFS 210 days, OST 354 days) and RBCHOP 2 (PFS 220 days, OST 456 days), but significantly shorter for RBCHOP 3 (PFS 34 days, OST 80.5 days, P  < 0.001). No presenting signalment nor hematologic variable differentiated patient cohort, however, dogs in RBCHOP 2 and RBCHOP 3 were more likely to have a lymphocytosis at diagnosis ( P  = 0.02 and 0.04, respectively). Protocol modification based on response during the first cycle resulted in similar toxicity profiles and outcomes to previously published variants of CHOP, and prognosis remained poor for dogs failing to respond during the first treatment cycle.